Reported morbidity and the weather - Peacock, J. B. (1975)
Some observations have been made about the influence of the weather on the use of the general-practitioner service. It is difficult to disentangle the biological and behavioural components of these findings, but in general extremes of weather—low temperatures and sunshine in winter and high temperatures and sunshine in summer—appeared to increase the numbers of reported episodes of respiratory illness.